Do pictures ‘tell’ a thousand words in lectures?: how lecturers vocalise photographs in their presentations - Hallewell, Madeline J.; Lackovic, Natasa (Taylor & Francis, 2017)
This article explores how 145 photographs collected from 20 PowerPoint lectures in undergraduate psychology at 16 UK universities were integrated with lecturers’ speech. Little is currently known about how lecturers refer to the distinct types of photographs included in their presentations. Findings show that only 48 photographs (33%) included in presentation slides were referred to explicitly by exploring their features to make a point related to the lecture content, with only 14 of these used to invite student questioning. Most photographs (97 or 67%) represent a case of ‘unprobed representations’, that is, either ‘embedded’ in the talk as ‘illustrations’ of the speech topic or not referred to at all. A taxonomy of uses that lecturers made of the photographs in their slideshows was created through adapting a Peircean semiotic analysis of the photograph–speech interaction. The implications in terms of lecturer and student engagement with the photographic material are discussed, arguing the case for more Critical Semiotic Exploration of photographs in HE practice.